2021
DOI: 10.2196/22999
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the COVID-19 Spread Through Real-time Population Mobility Patterns: Surveillance in Low- and Middle-Income Countries

Abstract: Background On January 21, 2020, the World Health Organization reported the first case of severe acute respiratory syndrome coronavirus 2, which rapidly evolved to the COVID-19 pandemic. Since then, the virus has also rapidly spread among Latin American, Caribbean, and African countries. Objective The first aim of this study is to identify new emerging COVID-19 clusters over time and space (from January 21 to mid-May 2020) in Latin American, Caribbean, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Two of the articles found varying results within the study, as Kartal, Depren, and Depren [ 32 ] noted park use as related to higher COVID-19 deaths but having no impact on cases. Tyrovolas et al [ 35 ], by contrast, found an overall pattern of park mobility indicating lower COVID-19 spread, except in areas of lockdown, where it was associated with higher spread. Of the four studies that found a positive association between park mobility and COVID-19 outcomes, two specifically noted that park results were weaker than other forms of mobility [ 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the articles found varying results within the study, as Kartal, Depren, and Depren [ 32 ] noted park use as related to higher COVID-19 deaths but having no impact on cases. Tyrovolas et al [ 35 ], by contrast, found an overall pattern of park mobility indicating lower COVID-19 spread, except in areas of lockdown, where it was associated with higher spread. Of the four studies that found a positive association between park mobility and COVID-19 outcomes, two specifically noted that park results were weaker than other forms of mobility [ 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Those more detailed results are provided in Appendix B . This closer look reveals a wide variation in locations included in this research, including one global study that also specifically addressed the regions of Africa, Latin America, and the Caribbean [ 35 ], and country-specific studies of England [ 31 ], India [ 34 ], Portugal [ 29 ], Turkey [ 32 ], and the US [ 30 , 33 ]. As previously noted, all studies used Google community mobility data that provided aggregated mobility scores for six sets of destinations: retail and recreation, grocery and pharmacy, parks, transit stations, workplaces, and residential destinations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations